On the Well-Posedness for the 3-D Micropolar Fluid System in Critical Fourier-Besov-Morrey Spaces (London Journal of Research In Science: Natural and Formal, 2024)
In the present paper, we study the Cauchy problem of the incompressible micropolar fluid system in R3. We show that this problem is locally well-posed in Fourier-Besov-Morrey spaces.
Keywords: Finite difference; mathematical induction; integral order; positive powers; arithmetic progression.; reproductive property.; 3-D micropolar fluid system; Fourier-Besov-Morrey spaces; well-posedness.